Behaviour of Sr, Ca, and Mg isotopes under variable hydrological conditions in high-relief large river systems. (15th February 2023) - Chen, Bei-Bei; Li, Si-Liang; Pogge von Strandmann, Philip A.E.; Wilson, David J.; Zhong, Jun; Ma, Ting-Ting; Sun, Jian; Liu, Cong-Qiang
Abstract: To assess how chemical weathering processes in large high-relief river systems respond to climatic variability, we studied seasonal changes in radiogenic strontium ( 87 Sr/ 86 Sr) and stable calcium (δ 44/40 Ca) and magnesium (δ 26 Mg) isotopes in the Jinsha and Yalong rivers, which drain the southeastern Tibetan Plateau. During the low-runoff season, with discharge (Q) < 2000 m 3 /s, the river waters reflect the Sr, Ca, and Mg isotope signatures of recharge meltwaters, with additional isotope fractionation signals for Ca and Mg related to secondary mineral precipitation, which might imply that meltwater flushes soil solutions from the soil. During medium-runoff intervals (2000 m 3 /s < Q < 4000 m 3 /s), the Sr, Ca, and Mg isotope signatures in the Jinsha river waters are similar to those of the headwaters, which are influenced by evaporite dissolution, while the Yalong is affected by greater carbonate weathering relative to silicate weathering. In both rivers, bedrock dissolution governs the chemical composition of the river waters. During the high-runoff season (Q > 4000 m 3 /s), storms generate rapid overland flow, which transfers large volumes of soil into the rivers, such that soil weathering plays an important role in regulating riverine chemical compositions. At these times, the riverine Ca and Sr isotope evolution is influenced by secondary mineral dissolution and sediment–water cation exchange. Overall, this study highlights the potential of combining multiple isotope systems (Sr, Ca, Mg) to trace the dynamics of water–rock interaction under variable hydrological conditions.